Impact of Lesson Study on Motivation and Achievement in Mathematics of Malaysian Foundation Programme Students - Hosseinali Gholami; Aida Suraya Md Yunus; Ahmad Fauzi Mohd Ayub; Nurzatulshima Kamarudin (USN Kolaka, 2020)
This quasi-experimental study was conducted to determine the impact of the implementation of lesson study on students' motivation in mathematics and mathematics achievement as well as gender in a public university in Selangor, Malaysia. Seven mathematics lecturers, a physic lecturer and researcher, formed a lesson study group. This group planned and designed five research lessons about the functions focusing on problem-solving. A lecturer was chosen randomly to teach these lessons to his classes as experimental and control groups. In this study, mathematics motivation test (5-point Likert-type scale ranging from 1 (not at all true) to 5 (very true)) and lecturers developed tests were used to investigate the impact of lesson study on mathematics motivation and achievement. The data were analyzed by using independent t-test, ANOVA test, MANOVA test and non-parametric the Kruskal-Wallis test. The results of this study showed thatstudents in the experimental group obtained better results in both motivation andachievement tests. Also, there is no statistically significant interaction between the effects of educational method and gender on mathematics achievement scores. Furthermore, the results showed that the level of motivation is different among groups by gender, but there were no significant mean differences among groups in any of subscales.